Levonorgestrel intrauterine system: A first line medical therapy for idiopathic heavy menstrual bleeding - Mahapatra, P.C.; Kapur, Anupam; Baxi, Asha; Kekre, Aruna; Mediratta, Geeta; Gajaraj, Jaishree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Heavy menstrual bleeding or menorrhagia is a common menstrual disorder. Currently, both medical and surgical treatment options are available for the management of heavy menstrual bleeding. Hysterectomy, one of the surgical treatment options is associated with risks and is a costly procedure. Medical treatment may be preferred for the management of heavy menstrual bleeding. Oral medical treatments have various limitations for their use. For instance, cost is a limiting factor for tranexamic acid. Limited data is available to support the effectiveness of oral contraceptives. Poor patient compliance and intolerable adverse events are some other limitations especially in long term use. Levonorgestrel intrauterine system (LNG-IUS) is one of the common medical modalities in the management of heavy menstrual bleeding. LNG-IUS has been compared with other medical options like tranexamic acid, mefenamic acid, combined estrogen-progestogen, or progesterone alone, cyclic oral medroxyprogesterone acetate (MPA) oral norethisterone and low-dose combined oral contraceptive. LNG-IUS is more effective than usual medical treatment and also reduces the effect of heavy menstrual bleeding on quality of life. Similarly, it has shown similar therapeutic effects compared to endometrial ablation. Based on its efficacy, convenience and cost of therapy, it can be considered as the first line medical therapy for the management of heavy menstrual bleeding.